Persepektif Hukum Islam Dalam Sistem Pembagian Sisa Hasil Usaha: (Studi Kasus di Koperasi Serba Usaha Giri Jaya Mete Kecamatan Jatisrono Kabupaten Wonogiri) - Malik, Ismi (Fakultas Syari'ah Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo., 2023)
The cooperative annually distributes the remaining operating results to its members. The distribution of the remaining operating income can also reflect the success or success of the cooperative. The purpose of this study is to find out the distribution system of the remaining operating income (SHU) in the Giri Jaya Mete Multipurpose Cooperative. Islamic law review. The research method used to discuss the profit sharing system in the perspective of Islamic law (Case Study in the Giri Jaya Mete Multipurpose Cooperative, Jatisrono District, Wonogiri Regency) is using field research methods and qualitative descriptive. Field research is research conducted by collecting data and information obtained directly from informants and observing directly related tasks. The SHU distribution system at KSU Giri Jaya Mete is in accordance with the AD/ART that has been determined during the RAT. The distribution of SHU between cooperatives and members in the form of a percentage of SHU is distributed at the end of the year, and is put into the savings of each member, the SHU obtained depends on how much the member's contribution to KSU Giri Jaya Mete In Islam the distribution of SHU is included in the mudharabah contract. KSU Giri Jaya Mete in the distribution of the remainder of its business results is in accordance with the mudharabah principles, namely the principle of sharing profits between the parties making the contract, then the principle of sharing losses between the contracting parties, the principle of clarity which is in distributing SHU, KSU Giri Jaya Mete always prioritizes being open and clear, so that all members can know the financial circulation of KSU Giri Jaya Mete.